Morphology and properties of pyrite nanoparticles obtained by pulsed laser ablation in liquid and thin films for photodetection - Parameswaran Sreekala, Akshana; Krishnan, Bindu; Cienfuegos Pelaes, Rene Fabian; Avellaneda, David Avellaneda; Aguilar-Martínez, Josué Amílcar; Shaji, Sadasivan (Beilstein Journal of Nanotechnology, 2025)
This work reports the synthesis of pyrite (iron disulfide (FeS2)) nanoparticles (NPs) of different morphologies using pulsed laser ablation in liquid (PLAL) in different organic solvents. The impact of the solvent on the morphological, compositional, and optical properties of the synthesized NPs is investigated by techniques such as transmission electron microscopy, scanning electron microscopy, X-ray photoelectron spectroscopy, and ultraviolet–visible spectroscopy. The morphology of the NPs in different solvents varied from spherical, rice-like to rod-like particles which demonstrates the effect of the solvent on the morphology/composition of NPs synthesized by PLAL. FeS2 NPs were successfully synthesized in five different solvents, along with a minor phase of iron sulfide (FeS). Additionally, by combining electrophoretic deposition and spin-coating techniques, thin film photodiodes of FeS2 were fabricated on an n-type Si substrate utilizing the nanocolloids. The structural, morphological and electrical characterizations of the films are also presented. By sulfurization of the films, phase-pure pyrite thin films are obtained. The photodetection range was up to 785 nm photocurrent in the order of 10−6 to 10−4 A for different annealing conditions and a detectivity in the order of 106–108 Jones is attained. The FeS2/n-Si photodetector works in self-powered mode also in addition to the photoconductive mode. The results show the effective fabrication of nanostructured ultraviolet–visible–near infrared thin film photodetectors using semiconductor nanocolloids prepared by PLAL.
Keywords: electrophoretic deposition; pulsed laser ablation in liquid; pyrite nanoparticles; self-powered photodetector; spin coating